Pengaruh Pembelajaran Blended Learning Menggunakan Tracker pada Materi Gerak Harmonis Sederhana Berbasis Inkuiri Terbimbing Terhadap Peningkatan Kemampuan Berpikir Kreatif Siswa - Alfayani, Cindy; Suana, Wayan; Viyanti, Viyanti (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2024)
This study aims to assess the influence of blended learning, along with a guided inquiry-based tracker app, on students' ability to think creatively. The main goal of the study is to quantify the extent to which this approach enhances students' capacity for original thought. The research design employed in this study is the One Group Pretest Posttest design. The research sample consisted of thirty-six students from SMAN 1 Gedongtataan's X Science 3 class. The instruction of fundamental harmonic motion on springs is facilitated through the utilization of a guided inquiry-based tracker application in a blended learning environment. The collection of data on students' creative thinking abilities involved the use of written assessments (Pretest-Posttest) and the analysis of this data using the Paired Sample T-Test. The research findings showed an N-Gain value of 0.20, which falls into the low range. Additionally, the paired sample T-test analysis revealed a statistically significant result with a sig (2-tailed) value of less than 0.05. The findings indicate that there were discernible variations in the creative cognitive abilities of students prior to and following their utilization of the tracker application. The results indicate that the usage of a guided inquiry-based tracker application in blended learning environments can improve students' ability to think creatively.